Analisis Pengetahuan PHBS dengan Pengelolaan Sampah Pada Siswa SMP Swasta Bina Siswa Laut Dendang - Indah Syahfitri Nasution; Dinda Ayumi Nasution; Dwene Nur Gianing; Dwi Irma Wulandari; Khairuzikria Ramadhani; Eliska Eliska (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Clean and Healthy Living Behavior is basically an effort to transmit experiences about healthy living behavior through individuals, groups or the wider community with communication channels as a medium for sharing information. There is a variety of information that can be shared such as educational materials to increase knowledge and improve attitudes and behaviors related to a clean and healthy way of life. This study aims to determine the behavior of SMP BINA SISWA students in implementing PHBS and waste management in schools. The design of this research is a quantitative descriptive research. The population of this study were all students of SMP BINA SISWA which consisted of three classes, namely class VII, VII, and IX. Data collection techniques in this study used questionnaires distributed to respondents. The results of the study indicate that most of the respondents have good knowledge about the implementation of PBHS in disposing of waste in its place.